Formation of students' skills in analyzing information graphs through constructive feedback (Journal of Educational Sciences, 2024)
The research topic examines the performance of 12th grade students from the Nazarbayev Intellectual School in Semey in passing external summative exams, comparable to international AS/A-Level standards. The summative assessment system was developed in collaboration with the Cambridge Assessment International Education Council and aims to measure the functionality of acquired knowledge and skills through a variety of tasks performed by students. The study also explores the international program for assessing educational achievements, such as PISA, among students in general education schools and Nazarbayev Intellectual Schools, focusing on mathematical and functional literacy. It was found that international exams like PISA and AS/A-Level often include visual organizers that require high-order thinking skills according to Bloom's taxonomy. Currently, tasks corresponding to this type of international exam are being introduced in schools and universities in Kazakhstan. Therefore, innovative teachers should possess pedagogical and psychological methods and strategies. One of them is the CLIL strategy, which involves using are often accompanied by information graphics as visual organizers and constructive feedback to help students understand and solve tasks in international exams. This research not only examined various visual organizers in summative assessment but also provided constructive feedback to 11th and 12th grade students in biology and computer science. The article also carefully analyzed the analytical reports of international exams.Key words: constructive feedback, graphic organizers, Bloom's taxonomy, competencies, interpretation.